An eigenvalue of anisotropic discrete problem with three variable exponents - Ousbika, M.; Allali, Z. El (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5 We study the existence of a continuous spectrum of an anisotropic discrete problem, involving variable exponent. The proposed technical approach is based on the variational methods and critical point theory.